Lenten Repentance in a Participatory-Synodal Journey: Strengthening the Life Orientation of the Priest of the Diocese of Bangka-Belitung - Antonius Moa (Abdimas Paspama, 2023)
Lenten repentance is a process of renewal of life orientation that does not stop at ascetic practice, but needs to be seen in the way Church ministers build relationships with God, others, and the ministry community. This Community Service activity aims to deepen repentance as metanoia and connect it with participatory-synodal spirituality for the priests of the Bangka-Belitung Diocese. The activity was held in Parittiga, West Bangka Regency, Bangka-Belitung Islands, on March 14, 2023 as part of the South Kevikepan Imam Meeting. The recollection session was attended by 39 participants, consisting of 27 diocesan priests, 3 religious priests, 1 deacon, and 8 brothers. The method of activities includes theological-interactive presentations, deepening the meaning of Lent, personal reflection, synodal dialogue, and afternoon worship. The results of the activities at the process level show the availability of a structured space for reflection, strengthening the understanding of communion, participation, and mission, and the affirmation of repentance as the basis for ministry renewal. This model of recollection is relevant for ongoing coaching because it combines theological foundations, pastoral experiences, community dialogue, and personal follow-up.